Pemanfaatan Model Informasi Bangunan dalam Manajemen Konstruksi Proyek Rumah Susun Vertikal di Bintaro - Melania Lidwina Pandiangan; Rahma Purisari; Khalid Abdul Mannan (I-Com: Indonesian Community Journal, 2024)
As construction technology advances, Building Information Modeling (BIM) has become a crucial tool for managing construction projects, including enhancing integration between disciplines such as architecture, structure, and MEP (Mechanical, Electrical, Plumbing). Through a community service initiative, the team from the Architecture Study Program at Universitas Pembangunan Jaya (UPJ) collaborated with construction management consultant on a residential apartment project in Bintaro. This activity involved BIM modeling in the architectural discipline to detect discrepancies between disciplines through clash detection. The modeling was carried out using Autodesk Revit 2024, and analysis was performed using Navisworks. The results of this activity demonstrate that the application of BIM effectively identifies and resolves design conflicts between disciplines at the planning stage. This collaboration has proven to enhance construction oversight efficiency and reduce the risk of errors on-site.